Features of Somatic Anamnesis and Reproductive Function in Women with Uterine Myoma and / or Adenomiosis and Methods of their Correction (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: uterine fibroids; adenomyosis; somatic morbidity; reproductive losses; childbirth; ultrasound and Doppler blood flow of myoma